2003
DOI: 10.1001/jama.289.20.2709
|View full text |Cite
|
Sign up to set email alerts
|

Use of Race and Ethnicity in Biomedical Publication

Abstract: Researchers, clinicians and policy makers face three challenges in writing about race and ethnicity: accounting for the limitations of race/ethnicity data; distinguishing between race/ethnicity as a risk factor or as a risk marker; and finding a way to write about race/ethnicity that does not stigmatize and does not imply a we/they dichotomy between health professionals and populations of color. Journals play an important role in setting standards for research and policy literature. The authors outline guideli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
473
1
25

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 510 publications
(513 citation statements)
references
References 83 publications
9
473
1
25
Order By: Relevance
“…22 Clearly, inter-racial and ethnic differences in polymorphisms of genes may exist, affecting susceptibility to diverse diseases. 23 Common, complex diseases show an unknown mode of inheritance, and differing ethnicity, along with other factors, could confound the pathogenesis of CAD. We speculate that our positive results may be partly owing to the finding that 82S allele frequencies of the RAGE gene are statistically higher in the Chinese Han population compared with other countries and ethnic groups.…”
Section: Discussionmentioning
confidence: 99%
“…22 Clearly, inter-racial and ethnic differences in polymorphisms of genes may exist, affecting susceptibility to diverse diseases. 23 Common, complex diseases show an unknown mode of inheritance, and differing ethnicity, along with other factors, could confound the pathogenesis of CAD. We speculate that our positive results may be partly owing to the finding that 82S allele frequencies of the RAGE gene are statistically higher in the Chinese Han population compared with other countries and ethnic groups.…”
Section: Discussionmentioning
confidence: 99%
“…En la literatura ya se ha indicado la necesidad de explicitar y justificar la práctica de cómo asignar la denominación étnica o racial de los participantes en los estudios (Kaplan y Bennett, 2003). Se han evaluado además las limitantes y ventajas de su uso en el marco de las hipótesis o propósitos de las investigaciones (Aspinall, 2001).…”
Section: Discusión Y Conclusionesunclassified
“…De hecho, se espera continuar esta línea de trabajo con una investigación sobre lo que dicen (conceptualizaciones y significados) y hacen los investigadores (mecanismos usados para "etiquetar" a las poblaciones) sobre la relación entre la etnoracialidad y la salud pública; estos estudios contribuirían a rastrear las influencias de las formaciones raciales en las investigaciones en salud en Colombia y, en últimas, "a encontrar la manera menos imprecisa para aproximarse, con fines descriptivos y estadísticos, a los conceptos sociales de raza y etnicidad" (Kaplan y Bennett, 2003:2711.…”
Section: Discusión Y Conclusionesunclassified
“…60 Genetic differences are greater within socially defined racial groups than between groups. 61 Additionally, it has been found that genetic diversity decreases in noncoding regions whereas diversity of coding nonsynonymous SNPs is lower in regions containing a known protein sequence motif in individuals of European origin. 62 Drug treatment may be tailored for greater effect if important genetic variation exists between racial and ethnic groups.…”
Section: Ethnicitymentioning
confidence: 99%